A case of metastatic malignant hemangiopericytoma of the ovary: Recurrence after a period of 17 years from intracranial tumor. Issue 5 (1st August 2002) - Begum, M.; Katabuchi, H.; Tashiro, H.; Suenaga, Y.; Okamura, H.
Abstract : Hemangiopericytoma is an uncommon vascular tumor. Primary or metastatic hemangiopericytoma of the ovary is extremely rare. A 48-year-old Japanese woman had a tumor in the neck. Simultaneously, a solid ovarian tumor was detected. She had received treatment for intracranial hemangiopericytoma 17 years previously. For the ovarian tumor, she underwent a total abdominal hysterectomy and bilateral salpingo-oophorectomy. The left ovarian tumor weighed 1510 g and its cut surface was solid without areas of hemorrhage or necrosis. It was microscopically composed of tightly packed tumor cells outside of many vascular vessels. One or two mitotic figures were counted per 10 high power fields. Immunohistochemically, vimentin was expressed but factor-VIII-related antigen, CD 31, and CD 34 were not expressed in the tumor cells. Electron microscopy showed that the tumor cells were grown outside of the endothelium-lined vascular spaces. A discontinuous external basal lamina was also observed. We present a case of metastatic malignant hemangiopericytoma of the ovary from a primary intracranial hemangiopericytoma with a long interval of 17 years.